1981
DOI: 10.3354/meps006213
|View full text |Cite
|
Sign up to set email alerts
|

Multiphasic Kinetics for D-Glucose Uptake by Assemblages of Natural Marine Bacteria

Abstract: D-Gl~cose-6-[~H] uptake kinetics for marine microbial assemblages were multiphasic when the kinetics were determined over a broad concentration range (10-'M to I O -~ M). Maximum uptake velocity (V,,,,) and the sum of half saturation constant (K,) and ambient glucose concentration (S,), (K, + S,), increased gradually as the range of glucose concentration was increased. In all seawater samples examined the lowest (K, + SJ values were 2-5 x lO-'M; highest values were as high as 5.9 X 104 M. Simple diffusion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
105
1
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(112 citation statements)
references
References 22 publications
5
105
1
1
Order By: Relevance
“…5c), supporting an earlier conclusion that met constitutes a representative DFAA (Zubkov et al 2003). The bioassay technique, although criticised because of the common multiphasic kinetics of a compound's uptake at concentrations significantly higher than ambient (Azam & Hodson 1981), is still considered applicable if measurements are made at very low added compound concentrations (Williams 1973, Ferguson & Sunda 1984. Based on our experiments using the technique in the open Atlantic Ocean, a linear relationship is likely (e.g.…”
supporting
confidence: 52%
“…5c), supporting an earlier conclusion that met constitutes a representative DFAA (Zubkov et al 2003). The bioassay technique, although criticised because of the common multiphasic kinetics of a compound's uptake at concentrations significantly higher than ambient (Azam & Hodson 1981), is still considered applicable if measurements are made at very low added compound concentrations (Williams 1973, Ferguson & Sunda 1984. Based on our experiments using the technique in the open Atlantic Ocean, a linear relationship is likely (e.g.…”
supporting
confidence: 52%
“…The multiphase uptake kinetics in oligotrophic marine bacteria was not shown to be attributable to a single transporter (17,18). However, it is tempting to speculate, as Muñoz-Marín et al…”
Section: Multiphasic Uptake Kinetics For Glucosementioning
confidence: 81%
“…Interestingly, the Pro1404-encoded sugar transporter exhibited multiphasic uptake kinetics, i.e., having low-affinity and high-affinity phases. This has not been observed before for sugar transport in cyanobacteria but has been observed in other oligotrophic marine bacteria (17,18) characterized the uptake kinetics for Prochlorococcus SS120 and found that it also exhibited multiphasic kinetics. Furthermore, they estimated the MichaelisMenton affinity constants and found that the high-affinity K s value (123 nM) and the low-affinity K s (0.9 μM) were the same for uptake in cultures of Prochlorococcus SS120 and for the Pro1404-encoded transporter in the recombinant S. elongatus PCC7942, adding further support to the role of Pro1404 gene in glucose uptake.…”
Section: Multiphasic Uptake Kinetics For Glucosementioning
confidence: 83%
“…Possibly, as discussed above, microorganisms in the productive Swedish lakes could be adapted to sporadic and local bursts of organic matter with a high content of amino acids, for example inputs linked to blooms of cyanobacteria. In the present study, we did not test for possible multiphasic uptake kinetics at high substrate concentrations (Azam and Hodson, 1981;Logan and Fleury, 1993). Such information could give a more complete understanding of the arginine-processing features of the microbial community, but would require incubations with a wider range of arginine concentrations than the 5-460 nm used in our study.…”
Section: Discussionmentioning
confidence: 99%